Unrecorded watermark, colour shade and perforation variation in philatelic issues commemorating the World Youth Stamp Exhibition (2014) from Malaysia - Das, I.; Genevieve, V. A. Gee (Philatelic Society of Kuching Sarawak, 2016)
A watermark is applied to an official paper document of value, such as postage and revenue stamps, bank notes and passports, as a device to reduce counterfeiting (Mackay, 2003). Typically, it comprises a pattern, image or letters that appear when viewed under transmitted light, or via reflected light on a dark background. Watermarks on postage stamps are often what differentiate a common stamp from a rare and valuable one, and recognition and study of watermarks is an active field of philately. Colour variation in stamps are more common and may be significant, especially in cases of missing colours. However, changelings (stamps that change colours due to condition of storage, etc) are of little philatelic value, and may be difficult to scientifically document (Guertin, 1965; Herendeen, 2013). Perforation types are also noteworthy, and recorded in detailed catalogues. As in watermarks, perforations can result in price differences between stamps, and fake perforations are common (Prill, 2011).